PHYSIOTHERAPHY MANAGEMENT ON PES ANSERINE BURSITIS CASE: A CASE STUDY - Harahap, Parida Amalia; Pristianto, Arif (Universitas Muhammadiyah Surakarta, 2021)
Introduction: Pes Anserine Bursitis (PAB) is an inflammation of pes anserine with the prevalence of this condition is 2.5% during 1998 to 2004 at a tertiary orthopaedic centre in United Kingdom. But, there is no exact number of pes anserine bursitis worldwide. The study cases of PAB with history of post knee arthroscopic surgery is limited. Moreover, PAB without any symptoms of inflammation except pain.Clinical Presentation: A man, 28 years old, actives in futsal and diagnosed with pes anserine bursitis, having only one session.of physiotherapy for 30 minutes by given therapy with an ice pack, ultrasound, gun massage, isometric exercise, and TENS. It is given once a week for one week only.Management and Oucome: Physiotherapy management such as ultrasound, gun massage, isometric exercise, and TENS could reduce pain on pens anserine bursitis problems. After follow 7 days of physiotherapy’s session, The NRS scale reduce from 4 to 0.Discussion: In this case, due to the patient’s sport activities, it could affect the perform of pes anserine-forming muscle. It could make the bursa inflammation and pain in the medial knee. After seventh day treatment, the pain was disappeared. Moreover, the patient did not have any functional limitation, decrease on strength muscle and range of motion, or any change of gait. A case study of a 79-year-old female with pes anserines bursitis who had undergone knee arthroplasty 13 years prior. She had knee pain for a year without any symptoms of infection, inflammation or history of trauma. She was treated with a combination of strengthening exercise, stretching exercise, and local steroid injection.Conclusion: The physiotherapy program could reduce the pain after having one therapy on the pes anserine bursitis problem.